Performance analysis of a combined updraft-stratified downdraft (CUSD) gasifier. - Vinluan, F.D. Jr.
The performance of the CUSD experimental gasifier was analyzed. The experimental was conducted at the Mechanical Engineering (M.E.) Power Laboratory, College of Engineering, University of the Philippines, Diliman, Quezon City. With the use of ipil-ipil wood chips as fuel, the CUSD gasifier was proven to have a favorable performance as evidenced by the heating value of the gas, color of the flame, specific gasification rate and gasification efficiency. The peak efficiency was obtained at L=0.15 which correspons to an airflow ratio (downdraft/updraft) of 7.34. The CUSD gasifier possesses some desirable features which give it advantages over single stage forced draft gasifiers. These features include continuous gas production during fuel feeding, stable reaction zones even without tuyeres and movable grate, clean gas being produced with the proper combination of downdraft and updraft airflow rates, and effective removal of ash even without a movable grate. If translated into the user's benefits, these features could mean lower initial investment cost, easier maintenance and simpler operation than existing designs.